A Perspective on Newly Emerging Proteolysis-Targeting Strategies in Antimicrobial Drug Discovery - Janarthanan Venkatesan; Dhanashree Murugan; Loganathan Rangasamy (MDPI AG, 2022)
Targeted protein degradation is a new aspect in the field of drug discovery. Traditionally, developing an antibiotic includes tedious and expensive processes, such as drug screening, lead optimization, and formulation. Proteolysis-targeting chimeras (PROTACs) are new-generation drugs that use the proteolytic mechanism to selectively degrade and eliminate proteins involved in human diseases. The application of PROTACs is explored immensely in the field of cancer, and various PROTACs are in clinical trials. Thus, researchers have a profound interest in pursuing PROTAC technology as a new weapon to fight pathogenic viruses and bacteria. This review highlights the importance of antimicrobial PROTACs and other similar "PROTAC-like" techniques to degrade pathogenic target proteins (i.e., viral/bacterial proteins). These techniques can perform specific protein degradation of the pathogenic protein to avoid resistance caused by mutations or abnormal expression of the pathogenic protein. PROTAC-based antimicrobial therapeutics have the advantage of high specificity and the ability to degrade "undruggable" proteins, such as nonenzymatic and structural proteins.